Radiological Configuration of the Vestibular Aqueduct Predicts Bilateral Progression in Meniere's Disease - Bächinger, David; Schuknecht, Bernhard; Dlugaiczyk, Julia; Eckhard, Andreas H. (Frontiers in Neurology, 2021)
Objective: Meniere's disease (MD) progresses from unilateral to bilateral disease in up to 50% of patients, often chronically and severely impairing balance and hearing functions. According to previous studies, 91% of bilateral MD patients demonstrate bilateral hypoplasia of the endolymphatic sac (ES) upon histological and radiological examination of their inner ears. Here, we seek to validate a radiological marker for ES hypoplasia that predicts the risk for future progression to bilateral MD in individual patients. Methods: Patients with unilateral MD and radiological evidence for ES hypoplasia in either the clinically affected inner ear (cohort MDuni-hpuni) or both inner ears (cohort MDuni-hpbi) were included. Given our hypothesis that ES hypoplasia critically predisposes the inner ear to MD, we expected progression to bilateral MD only in the MDuni-hpbi cohort. To investigate eventual progression to bilateral MD, clinical, audiometric, and imaging data were retrospectively collected over follow-up periods of up to 31 years. Results: A total of 44 patients were included in the MD-hpuni (n = 15) and MDuni-hpbi (n = 29) cohorts. In line with our radiology-based predictions, none (0/15) of the MD-hpuni patients exhibited progression to bilateral MD, whereas 20/29 (69%) MD-hpbi patients have already progressed to bilateral MD. Using the Kaplan–Meier estimator, bilateral disease progression would be observed in 100% of MD-hpbi patients 31 years after the initial diagnosis with an estimated median time to bilateral progression of 12 years. The nine MD-hpbi patients who, so far, remained with unilateral disease demonstrated a median time since initial (unilateral) MD diagnosis of only 6 years and are thus still expected to progress to bilateral disease. Conclusion: Progression to bilateral MD adheres to predictions based on the radiological presence or absence of ES hypoplasia. This prognostic tool, if validated by prospective long-term studies, will provide clinically relevant information about a patient's future disease burden and will help to select more personalized treatment regimens.